PENGARUH VIDEO EDUKASI TERHADAP SIKAP SISWA SEKOLAH DASAR TENTANG BENCANA GEMPA BUMI DI SDN 1 PUNDONG BANTUL YOGYAKARTA: The Effect Of Earthquake Disaster Educational Video On Attitudes Of Elementary School Students About Earthquake Disaster At Elementary School 1 Pundong, Bantul, Yogyakarta - Lismawati, Wulan Tri Mayang; Setyaningrum, Niken; Darmawan, Ardian Indra (Jurnal Kesehatan Masa Depan, 2023)
Background: Disaster is a natural or non-natural process that causes loss of life, property and disrupts the order of life, one of which is an earthquake. An earthquake is an event where the earth shakes due to collisions between the earth's plates, fault activity (fault), volcanic activity, or rock debris. Earthquakes can destroy buildings, roads, bridges and so on in an instant. Indonesia is a country that has the potential for natural disasters, one of which is an earthquake because Indonesia is at the confluence of three large plates, namely the Indo-Australian Plate, the Euro-Asian Plate and the Pacific Plate which causes Indonesia to be included in the Pacific Ring of Fire. World. Efforts to reduce the impact of the earthquake disaster are by increasing students' attitudes towards earthquake disasters through educational videos given early on to elementary school students, because children are vulnerable to the effects of disasters. Therefore it is very important to avoid or reduce the risk of victims. Objective: To determine the attitude of elementary school students towards earthquakes in grades 4 and 5 at SDN 1 Pundong Bantul Yogyakarta. Methods: This study used a pre-experimental research design with a one group pretest and posttest approach. The sample technique uses Total Sampling. The research population is SDN 1 Pundong Bantul Yogyakarta. With a sample of 37 respondents. Data analysis uses the Wilcoxon Signed Rank Test. Results: Results: there is an effect of educational videos on students' attitudes at SDN 1 Pundong Bantul with a p-value = 0.000 (<0.05). Conclusion: Students' attitudes about earthquake disasters can be improved with earthquake disaster educational videos.